Revegetation trials in degraded coastal marshes of the Hudson Bay Lowlands. - Handa, Tanya I. (Ottawa : National Library of Canada = Bibliothèque nationale du Canada, 1998)
Intense foraging by an increasing population of lesser snow geese, Anser caerulescens L., has led to the conversion of former salt-marsh swards, dominated by Puccinellia phryganodes and Carex subspothacea to hypersaline mudflats, and the conversion of former fresh-water sedge meadows, dominated by Carex aquatilis, to moss carpets. This study reports the potential for natural and assisted revegetation by the dominant graminoids of the former plant communities at La Perouse Bay, Manitoba in the absence of goose foraging. Natural recolonization by P. phryganodes was observed within five years where edaphic conditions were suitable. Transplants of P. phryganodes established readily in an intertidal marsh, and growth was enhanced by amelioration treatments of peat mulch and fertilizer to the soil surface. Natural recolonization by Carex subsparhacea was not observed. Transplants of the sedge did not establish readily in an inland marsh and amelioration treatments showed no effect. In fresh-water areas, tillers of Carex aquatilis established readily in moss carpets and growth was not enhanced by fertilizer application. The potential for revegetation is discussed within the context of vegetational succession and the ongoing degradation processes.